2014
DOI: 10.1093/jjco/hyu083
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control by Photo Documentation for Evaluation of Laparoscopic and Open Colectomy with D3 Resection for Stage II/III Colorectal Cancer: Japan Clinical Oncology Group Study JCOG 0404

Abstract: Completion of high quality surgery with D3 resection was confirmed in JCOG0404 by central peer review of photographs of the surgical procedures in addition to operator regulations. This study suggests that the central review of the photo documentation is one of the important tools to assure a quality control of surgical technique in the Phase III randomized-controlled study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 24 publications
2
17
0
1
Order By: Relevance
“…Results of the search: The initial electronic and manual literature searches revealed 174 full-text articles. A total of one RCT (from Japan)[ 20 , 21 ] and eleven CCTs (four from Europe and seven from Asia)[ 22 - 32 ] met the inclusion criteria for the qualitative and quantitative (meta-analysis) synthesis; these studies involved 1619 patients in L-CME and 1477 patients in O-CME. Eleven studies were published in English and one in Chinese.…”
Section: Resultsmentioning
confidence: 99%
“…Results of the search: The initial electronic and manual literature searches revealed 174 full-text articles. A total of one RCT (from Japan)[ 20 , 21 ] and eleven CCTs (four from Europe and seven from Asia)[ 22 - 32 ] met the inclusion criteria for the qualitative and quantitative (meta-analysis) synthesis; these studies involved 1619 patients in L-CME and 1477 patients in O-CME. Eleven studies were published in English and one in Chinese.…”
Section: Resultsmentioning
confidence: 99%
“…For quality control, the trial ensured that the surgeries were carried out by accredited surgeons, and a central review of each surgery was done on the basis of photographs obtained during the procedure. For the JCOG0404 trial, Nakajima et al reported that for right‐sided tumors, the proportion of D3 dissections was 98.5% (131/133) in OP and 100% (136/136) in LAP, and for left‐sided tumors, the proportion was 97.9% (322/329) in OP and 98.2% (320/326) in LAP, as evaluated by central review . Because quality of surgery is one of the important factors of surgery‐related adverse events, in terms of the proportion of D3 dissections carried out by accredited surgeons, the quality of surgery in the present study was high.…”
Section: Discussionmentioning
confidence: 99%
“…After 2008, an endoscopically surgically qualified surgeon according to JSES was added as an indispensable board member. Submission of photographs of the resected field after D3 lymph node dissection, the specimen, and the skin incision in all patients was required for central review of the surgical procedure . Primary endpoint was overall survival.…”
Section: Methodsmentioning
confidence: 99%